Spatial Attention Shifts in Addition and Subtraction Arithmetic: Evidence of Eye Movement. (September 2019) - Zhu, Rongjuan; You, Xuqun; Gan, Shuoqiu; Wang, Jinwei
Recently, it has been proposed that solving addition and subtraction problems can evoke horizontal shifts of spatial attention. However, prior to this study, it remained unclear whether orienting shifts of spatial attention relied on actual arithmetic processes (i.e., the activated magnitude) or the semantic spatial association of the operator. In this study, spatial–arithmetic associations were explored through three experiments using an eye tracker, which attempted to investigate the mechanism of those associations. Experiment 1 replicated spatial–arithmetic associations in addition and subtraction problems. Experiments 2 and 3 selected zero as the operand to investigate whether these arithmetic problems could induce shifts of spatial attention. Experiment 2 indicated that addition and subtraction problems (zero as the second operand, i.e., 2 + 0) do not induce shifts of spatial attention. Experiment 3 showed that addition and subtraction arithmetic (zero as the first operand, i.e., 0 + 2) do facilitate rightward and leftward eye movement, respectively. This indicates that the operator alone does not induce horizontal eye movement. However, our findings support the idea that solving addition and subtraction problems is associated with horizontal shifts of spatial attention.